Pengaruh Motivasi Belajar Terhadap Hasil Belajar Bahasa Indonesia Siswa Kelas VIII SMP Negeri 3 Tualang - Sepsena, Nola; Alber, Alber (UIR Press, 2023)
This research is motivated by learning motivation towards students' learning outcomes in Indonesian at school. Education is a process carried out by a person or individual to achieve an effective learning process with the aim of educating students to develop knowledge. In the maximum learning process can not be separated from the relationship with motivation. With the existence of motivation can support a learning process, in other words motivation as a driving force for students to carry out a learning activity. The methods used in this research are correlation and descriptive methods. The source of this research is population and sample. The approach used in this research is quantitative research. Data collection techniques used are observation techniques, interview techniques, and questionnaire techniques. This study uses data analysis techniques in the form of normality tests, linearity tests, simple linear regression tests. The results of data processing found in this study are the results of data analysis of learning motivation on Indonesian language learning outcomes for students' drama materials obtained r = 0.228, by obtaining df = 93, then tcount = 2.263 > ttable = 1.661 so that Ha is accepted and H0 is rejected which means that there is an influence of learning motivation on the results of learning Indonesian drama material.